Growth and development of symbiotic Arbuscular mycorrhizal fungi, Glomus mossea (Nicol. and Gerd.), in alachlor and glyphosate treated soils - Pasaribu, Askif; Mohamad, Rosli; Awang, Yahya; Othman, Radziah; Puteh, Adam (Academic Journals, 2011)
Herbicides are applied to control weeds in agricultural practices and could also be detrimental to the development of some microorganisms living in the soil ecosystem. This study was conducted to determine the growth and development of mycorrhizal fungi, Glomus mossea (Nicol. and Gerd.), in soils treated with herbicides. Herbicide treatments were alachlor at 1.8, 3.6, 5.4 and 36 μg active ingredient (a.i.) g-1 or glyphosate at 1.1, 2.2, 3.3 and 21.6 μg a.i. g-1 dry soil, representing 0.5, 1, 1.5 and 10 ´ their recommended field application rates. Spore germination percentage and hyphal growth length were determined from spores germinated on cellulose membrane filters, sandwiched between the herbicide treated soil layers in Perti-dish after 30 days incubation in darkness at 22±1°C. External and internal hyphae and their active portions were determined from soil samples of the host growing medium and colonized host plant root systems, respectively. The alkaline phosphatase (ALP) and succinate dehydrogenase (SDH) staining techniques were used to determine the respective active portion of the hyphae. Spores from the prepared inoculum source have high germination percentage (93%) in non-herbicide treated soil. Germination of spores and its hyphal growth were not significantly affected in soil treated with alachlor and glyphosate at the recommended field application rates or less. Alachlor reduced the spore germination and hyphal growth significantly at treatments higher than recommended field application rates, but non-significant effect caused by the glyphosate. The development of external hyphae was insignificantly affected in the herbicides treated soils compared with that of the untreated soil. Colonization and development of internal hyphae on host plant roots were not affected by the herbicide treatments to the soil growing medium at recommended field application rates or less. There was a tendency for the higher treatment rates of alachlor (1.5 and 10´) to affect the development of internal mycorrhizal tissues. Application of alachlor or glyphosate herbicide at their recommended field application rates were not harmful to mycorrhizal development and symbiotic colonization of plant roots. Alachlor, at higher treatments than the recommended field application rates affected the pre-symbiotic stages of the spore germination and the internal mycorrhizal tissues development substantially.